An Exploration Into China’s Intellectual Property Rights Protection - Lu, Melody Zhi Lin (2003)
In this paper I consider importance of IPRs system in international business, technology transfer, and the controversial issues regarding to IPRs, and the historical perspective of IPRs. IPRs can be an important stimulus to international business, innovation and economic growth if structured correctly and introduced in an environment of active competition. Then, I present the China’s recent and ongoing reforms in intellectual property rights through literature review, previous researches, indicating outstanding issues. Overall, the new legal regime seems meet the international standard, but there are some discrepancies that raise questions about policy, and difficulties in enforcement, whether it sensible for China’s position. The current IPRs situation in China is analyzed, based on interviews of public officials, enterprise managers, and scholars. China has implemented a strong set of laws but there remain problems with enforcement. A final section indicates few areas, such as the extent of public intervention, and the appropriate IP protection in China, which should be attract more research attention.